Autoimmune encephalitis associated with anti-LGI1 antibody: a potential cause of neuropsychiatric systemic lupus erythematosus - Chen, Sixian; Ren, Haitao; Fan, Siyuan; Zhang, Shangzhu; Li, Mengtao; Guan, Hongzhi (Lupus science & medicine, 2025)
ObjectiveTo investigate the clinical features and treatment outcomes of anti-leucine-rich glioma-inactivated 1 (anti-LGI1) encephalitis in patients with SLE.MethodsBetween October 2014 and April 2024, serum or cerebrospinal fluid samples were collected from 332 patients with SLE suspected of autoimmune encephalitis. Cell-based assays were used to detect autoimmune antibodies, including anti-LGI1 antibodies. Four patients tested positive for anti-LGI1 antibodies, and their clinical, radiological and treatment data were analysed.ResultsAll four patients exhibited signs of limbic encephalitis, including short-term memory deficits, seizures and psychiatric disturbances. Two cases also presented with faciobrachial dystonic seizures. MRI findings revealed hyperintense basal ganglia lesions in two patients. Treatment with corticosteroids, intravenous immunoglobulin and mycophenolate mofetil led to significant improvement in three patients, with no relapses during a follow-up period ranging from 33 to 60 months. One patient succumbed to pneumonia despite initial improvement of neurological function.ConclusionScreening for anti-LGI1 antibodies in patients with neuropsychiatric systemic lupus erythematosus (NPSLE) is crucial when limbic encephalitis presents, as it enables timely and effective treatment, potentially improving patients’ outcomes. Additional basic and clinical research is required to clarify the pathogenic role of these antibodies in NPSLE.